2014
DOI: 10.1038/nphoton.2014.189
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive single-shot imaging through scattering layers and around corners via speckle correlations

Abstract: Imaging with optical resolution through and inside complex samples is a difficult challenge with important applications in many fields. The fundamental problem is that inhomogeneous samples, such as biological tissues, randomly scatter and diffuse light, impeding conventional image formation. Despite many advancements, no current method enables to noninvasively image in real-time using diffused light. Here, we show that owing to the 'memory-effect' for speckle correlations, a single image of the scattered ligh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
721
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 946 publications
(729 citation statements)
references
References 54 publications
(143 reference statements)
4
721
0
4
Order By: Relevance
“…The latter approach was first developed for imaging through opaque barriers [13][14][15], and also allows for imaging around corners [16,17]. The work of Velten et al [5] and, more recently, Buttafava et al [8] sets out to establish the 3D shape of a static hidden object by collecting the return scattered light with a streak camera or single-photon avalanche diode, respectively.…”
mentioning
confidence: 99%
“…The latter approach was first developed for imaging through opaque barriers [13][14][15], and also allows for imaging around corners [16,17]. The work of Velten et al [5] and, more recently, Buttafava et al [8] sets out to establish the 3D shape of a static hidden object by collecting the return scattered light with a streak camera or single-photon avalanche diode, respectively.…”
mentioning
confidence: 99%
“…However, this technique requires a long angularscanning acquisition sequence, which limits its use to relatively static samples. Based on the same speckle-correlations and inspired by the astronomical technique of stellar speckle interferometry, Katz et al [15] have demonstrated that objects hidden behind scattering layers can be retrieved from the autocorrelation of a single high-resolution scattered light image, captured by a standard camera, via iterative phase-retrieval algorithms [16,17]. The single-shot technique benefits from a short acquisition time, which makes it possible to realize real-time imaging.…”
mentioning
confidence: 99%
“…But last year, a team led by Sylvain Gigan, a physicist at the Kastler Brossel Laboratory in Paris, and including Katz and Fink, demonstrated a way to reconstruct the image of the hidden object in just one camera shot 7 . "It's a bit like magic when you see the algorithm converge on the final image, " Gigan says.…”
Section: Inside Outmentioning
confidence: 99%